2016
DOI: 10.1039/c5ay03284a
|View full text |Cite
|
Sign up to set email alerts
|

A novel voltammetric sensor employing zinc oxide nanoparticles and a new ferrocene-derivative modified carbon paste electrode for determination of captopril in drug samples

Abstract: A novel ferrocene-derivative (1,l′-bis(2-phenylethan-1-ol)ferrocene) as a catalyst for the voltammetric determination of captopril in pharmaceutical and biological compound analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…In comparison to other analytical methods, electrochemical methods have attracted more attention in the recent years for electroactive and even nonelectroactive compounds analysis due to their good linear dynamic range and limit of detection, accuracy and lower cost . Therefore, electrochemical methods were used as performance techniques for determination of some biological, environmental and pharmaceutical compounds in recent years . To the best of our knowledge, a few numbers of studies has been reported on the voltammetric determination of curcumin using modified electrodes , which is the focus of the present study.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to other analytical methods, electrochemical methods have attracted more attention in the recent years for electroactive and even nonelectroactive compounds analysis due to their good linear dynamic range and limit of detection, accuracy and lower cost . Therefore, electrochemical methods were used as performance techniques for determination of some biological, environmental and pharmaceutical compounds in recent years . To the best of our knowledge, a few numbers of studies has been reported on the voltammetric determination of curcumin using modified electrodes , which is the focus of the present study.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24] The fabrication of the working electrode with nanoparticles enhances peak current, sensitivity, reproducibility. 25,26 In current science and technology, one of the crucial uniqueness is to survey and to discover the new efficient materials as electrode surface modifiers.…”
mentioning
confidence: 99%
“…As depict in Figure S1, the oxidation peak current of SOT is linearly correlated with scan rates; I p (μA)=−20 μA+10.241 μA/(Vs −1 ) 1/2 ; R 2 =0.9990. This behaviour indicates that, the electrochemical oxidation of SOT is controlled by diffusion processes .…”
Section: Resultsmentioning
confidence: 99%